2004
DOI: 10.1111/j.1468-3148.2004.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Research Implications of an Investigation into Theory of Mind (TOM) Task Performance in Children and Adults with Non‐specific Intellectual Disabilities

Abstract: Background Theory of Mind (TOM) has rarely been studied in people with intellectual disabilities. Wherever it has been studied, differing results have been found. These may be attributed to a variety of factors (e.g. the different chronological ages of samples). The validity of relating TOM performance to social behaviour has also been questioned in this population. The aim of this study was to compare TOM scores with chronological age and social ability in an attempt to contribute to current debate. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 27 publications
0
6
0
4
Order By: Relevance
“…ToM abilities lead to better social interaction and adjustment ( Charman and Campbell, 1996 , 2002 ; Barisnikov et al, 2002 ; Abbeduto and Murphy, 2004 ; Jervis and Baker, 2004 ; Deneault and Ricard, 2013 ). More particularly, some specific and variable links have been emphasized between, on the one hand, affective and cognitive ToM abilities in children with IDs, and on the other hand, their social or prosocial behavior during interactions with peers and adults as perceived by teachers ( Fiasse and Nader-Grosbois, 2012 ; Thirion-Marissiaux and Nader-Grosbois, 2008c ) or observed in dyadic play ( Baurain and Nader-Grosbois, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…ToM abilities lead to better social interaction and adjustment ( Charman and Campbell, 1996 , 2002 ; Barisnikov et al, 2002 ; Abbeduto and Murphy, 2004 ; Jervis and Baker, 2004 ; Deneault and Ricard, 2013 ). More particularly, some specific and variable links have been emphasized between, on the one hand, affective and cognitive ToM abilities in children with IDs, and on the other hand, their social or prosocial behavior during interactions with peers and adults as perceived by teachers ( Fiasse and Nader-Grosbois, 2012 ; Thirion-Marissiaux and Nader-Grosbois, 2008c ) or observed in dyadic play ( Baurain and Nader-Grosbois, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Schalock et al (2011) highlighted a delay in the acquisition of the first and second order false belief reasoning—i.e., the ability to engage in complex levels of recursive thinking—in a sample of children with moderate ID. Moreover, Jervis and Baker (2004) discovered that children with non specific ID had better performance on ToM tasks compared to adults with equal intellectual capacity. This would be due to the increment in social isolation that occurs over the years and that is frequently associated with ID.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of adults with learning disabilities, Charman & Campbell () found that only 13% of adults with non‐specific learning disabilities could successfully complete Theory of Mind tasks. Finally, Jervis & Baker () concluded from their extensive study that children with learning disabilities achieved significantly higher Theory of Mind scores than adults with learning disabilities. They also found that there was a positive relationship between children's Theory of Mind abilities and sociability.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that there was a positive relationship between children's Theory of Mind abilities and sociability. It has also been suggested that a lack of social opportunities for adults with learning disabilities may have led to lower levels of Theory of Mind ability (Jervis & Baker ). In summary, there is considerable evidence that some people with learning disabilities have difficulties with acquiring mature levels of Theory of Mind.…”
Section: Introductionmentioning
confidence: 99%